2017
DOI: 10.12659/msm.902454
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of Immunoreceptor Tyrosine-Based Inhibitory Motif (TIGIT) on T Lymphocytes is Correlated with Disease Activity in Rheumatoid Arthritis

Abstract: BackgroundIt is well known that lymphocytes play an important role in rheumatoid arthritis (RA). T cell immunoreceptors with immunoglobulin (Ig) and immunoreceptor tyrosine-based inhibitory motif (TIGIT) have immunosuppressive co-stimulatory molecules that mediate inhibitory effects, but their roles in RA are poorly understood.Material/MethodsWere recruited 76 patients with RA and 33 healthy controls (HC). Clinical manifestations, laboratory measurements, physical examination, and medical history of RA patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…RA is a systemic autoimmune disease with unknown etiology. In previous decades, great efforts have been made to explore the molecular mechanisms of RA [13,14]; however, the majority of previous studies have concentrated on protein-coding genes. Rapidly accumulating evidence has now suggested that although noncoding RNAs do not directly encode proteins, they play a regulatory role in the transcription and translation of protein-coding genes [15].…”
Section: Discussionmentioning
confidence: 99%
“…RA is a systemic autoimmune disease with unknown etiology. In previous decades, great efforts have been made to explore the molecular mechanisms of RA [13,14]; however, the majority of previous studies have concentrated on protein-coding genes. Rapidly accumulating evidence has now suggested that although noncoding RNAs do not directly encode proteins, they play a regulatory role in the transcription and translation of protein-coding genes [15].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of TIGIT on the surface of CD4+ T cells was recently shown to be associated with a higher DAS28 and increased evidence of inflammation in RA patients (27). Given that T cell activation results in the transient up-regulation of some inhibitory receptors (18), it is likely that the TIGIT+ T cells identified by Luo and colleagues (27) include activated T cells with increased potential to proliferate and produce effector cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of TIGIT on the surface of CD4+ T cells was recently shown to be associated with a higher DAS28 and increased evidence of inflammation in RA patients (27). Given that T cell activation results in the transient up-regulation of some inhibitory receptors (18), it is likely that the TIGIT+ T cells identified by Luo and colleagues (27) include activated T cells with increased potential to proliferate and produce effector cytokines. In contrast, our results indicated that the inhibitory receptor-expressing CD8+ T cells from RA patients with low levels of T cell activation are more likely undergoing terminal differentiation (i.e., exhaustion), a T cell differentiation stage associated with sustained expression of multiple inhibitory receptors (28).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, TIGIT expression on CD4 + T cells is elevated in patients with rheumatoid arthritis and systemic lupus erythematosus. [17][18][19] However, TIGIT expression on CD4 + T cells was augmented in patients with mild AD but reduced in those with severe AD, suggesting that TIGIT expression may be impaired in a subset of patients with AD, leading to the deterioration of skin inflammation.…”
Section: Discussionmentioning
confidence: 99%